Morphochemical Composition of Soil Microplastics in Lampung Landfill Using Microscopy and FTIR Spectroscopy Method - Lika Dini Almayda; Marlina Kamelia; Ade Lenty Hoya (Universitas Labuhanbatu, 2025)
Background: Plastic debris smaller than 5 mm is categorized as microplastic, a pollutant with persistent characteristics that often contains toxic or carcinogenic compounds. These particles can infiltrate soil systems, migrate into the food chain, and ultimately threaten both environmental integrity and human health. This research focuses on identifying the types and quantifying the abundance of microplastics in soils collected from three final disposal sites in Lampung Province, Indonesia. Methodology: Sampling at three landfill points was carried out purposive sampling method, with microplastics sample analyzed through visual inspection by microscopy and polymer composition confirmed using Fourier Transform Infrared (FTIR) Spectroscopy Method. Findings: Landfill sites B1 and C1 exhibited the highest abundance of microplastics, reaching 195 particles per kilogram of soil. The particles displayed morphological diversity, including fragments, fibers, and films, with fragments representing the predominant category. The color distribution was largely transparent, black, and brown, while the detected particle sizes ranged from 2.12 to 110.25 μm. Polymer analysis revealed the presence of polyethylene (PE), polyamide, and polystyrene, alongside particles suspected to be polyethylene terephthalate (PET). These findings indicate that physical and chemical degradation processes accelerate the breakdown of plastics into smaller fragments, thereby contributing to elevated microplastic levels in landfill soils. Contribution: The outcomes of this research, derived from visual microscopy and FTIR Spectroscopy-based identification of microplastics in Lampung landfill soils, The findings offer essential data for the development of monitoring frameworks and risk assessment strategies related to soil and environmental risks in the region